The human pressure on the middle Vistula River wildlife: the number and distribution of people and their activity on the river during the breeding season of birds - Bukaciński, Dariusz; Bukacińska, Monika; Mastalerz, Ewelina (Studia Ecologiae et Bioethicae, 2020)
The study aimed to determine the distribution, numbers, and forms of human activity on the banks and in the riverbed of the middle part of the Vistula River. This section of the river is the most valuable for nature and is located between Puławy and the mouth of the Pilica River (km 373-548 of the navigation route). Censuses were conducted in May-June 2014 and 2015, the breeding season of the key species of the riverbed avifauna. The presence and different forms of human activity were recorded, including fishing, camping, water tourism, hiking, motorized tourism, and grazing animals. The frequent presence of people on the Vistula River was much greater in June than in May. In both months, the most popular form of spending time by humans in the riverbed was fishing. While in areas less valuable for birds, fishing strongly dominated, on parts of the river with key breeding habitats for birds, more aggressive forms of recreation, camping and motorized tourism (quads, motorcycles, off-road vehicles), were reported as often or even more frequently. The increasing popularity of these forms of recreation is a very serious threat to the fauna. They not only disturb the breeding birds but also physically destroy breeding habitats and nests with eggs and increase the mortality of chicks of gulls, terns, and other waders.